Labor in the time of Trump - Kerrissey, Jasmine, 1977-; Weinbaum, Alys Eve, 1967-; Hammonds, Clare; Juravich, Tom; Clawson, Dan (ILR Press, an imprint of Cornell University Press, 2019)
"The labor movement has been under attack for decades; by understanding the nature of the right-wing attack, activists and scholars can analyze ways to build a working-class movement in the United States"-- Provided by publisher.
Keywords: Labor movement -- United States -- History -- 21st century.; Labor unions -- Political activity -- United States -- History -- 21st century.; Working class -- United States -- History -- 21st century.; United States -- Politics and government -- 2017-2021.; Mouvement ouvrier -- États-Unis -- Histoire -- 21e siècle.; Syndicats -- Activité politique -- États-Unis -- Histoire -- 21e siècle.; Travailleurs -- États-Unis -- Histoire -- 21e siècle.; États-Unis -- Politique et gouvernement -- 2017-2021.; POLITICAL SCIENCE / Labor & Industrial Relations; Labor movement; Labor unions -- Political activity; Politics and government; Working class; United States; 2000-2099; Electronic books.; History